Ecology of the Greater Sandhill Crane in Central Wisconsin - Howard, Thomas Jackson (University of Wisconsin-Stevens Point, 1977)
This study was designed to obtain information pertinent to greater sandhill crane (Grus canadensis tabida) productivity, habitat requirements, distribution, and seasonal abundance to facilitate management of the species. The field study was conducted in the central Wisconsin sand counties and was designed to investigate characteristics associated with greater sandhill crane reproduction and breeding habitat in central Wisconsin. Other objectives of the study included determinations of greater sandhill crane distribution and abundance in Wisconsin and identification of migration routes, staging areas, and wintering areas of Wisconsin's greater sandhil cranes. Fifty sandhill crane nests were located by helicopter early in the nesting seasons of 1974 and 1975. The mean size of marshes occupied by nesting cranes was 31.5 ha (1.6-151.8 ha). Dominant vegetation in these marshes included Sphagnum spp., Carex rostrata, Scirpus cyperinus, Carex lasiocarpa, Salix spp., Typha latifolia, Spirea tomentosa, Carex oligosperma, and Calamagrostis canadense. These species comprised over 80 percent of the vegetation present within 10 m of nests. Nests averaged 91 cm in diameter (65-125 cm), 16.9 em in height (7-31 cm), and were located in sites which averaged 12.55 cm in water depth (0.13-31. 88 em). Nests averaged 1714 m from sources o£ human activity (305-5630 m), 280 m from open water (11-1280 m), and 785 m from the nearest road (100-1905 m). Hatching occurred from 17 May to 17 June and shell thickness of eggshells averaged 0.26 mm (0.20-0.36 mm). Seventy percent of the eggs hatched between 19 and 30 May. Average clutch size was 1.84 and hatching success was 80.44 percent. Seventy-seven cranes were captured and color-marked with patagial tags in central Wisconsin during premigration staging. All captured cranes belonged to the tabida subspecies. Sightings of color-marked cranes indicated that the major flyway staging area of marked cranes during fall migration is the Jasper-Pulaski Refuge in northwestern Indiana and that their major wintering area is in the north-central prairies and marshes of Florida and southern Georgia. A mail survey was conducted through the Wisconsin Department of Natural Resources during June and July of 1975. A Wisconsin resident population of 780 adults (including 223 pairs) and 118 young of the year was reported. No cranes were reported from 26 counties, and 12 counties in central Wisconsin (Wood, Adams, Marquette, Green Lake, Portage, Marathon, Juneau, Clark, Columbia, Shawano, Jackson, and Monroe) accounted £or over 75 percent of the cranes reported.